Are we now observing an increasing number of coinfections between SARS-CoV-2 and other respiratory pathogens? - Sánchez-Duque, Jorge A. (2020)
We have recently read the article by Chaung et al1 describing a case of SARS‐CoV‐2 and HCoV‐HKU1 coinfection. The HCoV‐HKU1 is also a member of the Betacoronavirus. In addition to other coronaviruses in different regions of the world, there is an increasing number of reports of coinfections in SARS‐CoV‐2/COVID‐19. Then, we would like to take the opportunity to discuss some of them,1-10 as there are not yet reviews on this emerging issue of COVID‐19. Currently, the evidence suggests that the coinfection rates between SARS‐CoV‐2 and other respiratory pathogens would be higher than initially expected, which represents a challenge for the diagnosis and treatment.